MEMBANGUN MASA DEPAN PENDIDIKAN INDONESIA : PROSPEK KURIKULUM MERDEKA - Isye Legita Nurholiyah; Eneng Indri Herliani; Muhamad Rifki; Mulkiyah Mulkiyah; Mutiara Jasmine Maulana; Salwa Azzahra; Endah Ratna Sonya (IBERS : Jurnal Pendidikan Indonesia Bermutu, 2023)
Indonesia has implemented the Merdeka Curriculum, a new curricular framework designed to recover learning loss resulting from the COVID-19 pandemic and raise educational standards. The curriculum is created with a more flexible structure that places emphasis on character development and required subjects. Three categories of learning activities are included in the Independent Curriculum: extracurricular learning, intracurricular learning, and community service. Qualitative research design, a type of library research used in this research. The qualitative research design of this type of library research is research carried out using library research, which includes scientific research journals, books, notes and reports of research results that have been carried out by previous researchers. The Covid-19 pandemic in Indonesia has caused significant changes in several sectors, the education sector being the most affected. Seeing the current situation, the Ministry of Education and Culture is willing to continue the education program. One of the steps taken to overcome this problem is to change the name of the curriculum to "Independent Curriculum". The Independent Curriculum is a curriculum that includes various kinds of intracurricular learning activities. Regarding the implementation of the independent curriculum. In the implementation of the Merdeka curriculum, of course it is not immediately implemented directly. The initial launch of the Merdeka curriculum was in accordance with the policy issued by Minister of Education and Culture Regulation No. 3 of 2020 concerning National Education Standards for Higher Education. The independent learning curriculum is a curriculum that gives teachers the freedom to determine open tools that suit students' learning needs and demands. The implementation of the independent curriculum is inseparable from various challenges, including the obvious ones, namely, challenges to the readiness of teaching staff or teacher resources and also challenges to the readiness of teaching institutions, challenges in strengthening communication networks, and also challenges in carrying out the learning assessment function.